Bottomonia: open bottom strong decays and spectrum - Santopinto E. (EPJ Web of Conferences, 2014)
We present our results for the bottomonium spectrum with self energy corrections. The bare masses used in the calculation are computed within Godfrey and Isgur’s relativized quark model. We also discuss our results for the open bottom strong decay widths of higher bottomonia in the 3P0 pair-creation model.